Analisis Pengaruh Unsur Lingkungan Pengendalian (Control Environment) terhadap Keandalan Laporan Keuangan - Agung Budiartono (STIE Widya Manggala, 2020)
This study aimed to examine the effect of the Control Environment to reliability of Ministry / Agency financial statements in Indonesia. The elements of Control environment are tested, there are integrity and ethic value, commitment to competence, Supporting leadership, Organizational Structure, Authority and Responsibility, Human Resources Policy, The effectiveness of Government internal Audit, and Relationship with other agency. The population of this study are all the ministry/agency in Indonesia, and each of Ministry/ agency is represented by a person who presenting financial statements as respondents. The data in this study use primary data obtained from questionnaires distributed directly to the respondent. The Data collected are 59 questionnaires, from 86 questionnaires were distributed. The Data was analyzed using SmartPLS 3.0. The result shows that from 8 variables of Control Environment, only 2 that have effect to reliability of financial statements, there are The effectiveness of Government Internal Audit and Relationship with other agency. While others variables such as integrity and ethic value, commitment to competence, Supporting leadership, Organizational Structure, Authority and Responsibility, Human Resources Policy doesn’t have effect to reliability of ministry / agency financial statements.